JUSTIFIED AND UNJUSTIFIED PROHIBITED CLAUSES IN SERBIAN LAW ON “NON-POSSESSORY” PLEDGE - Lazic, Miroslav R (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
A “non-possessory” pledge is a common name for several pledge rights arising from the entry of such rights in the Pledge Register, without transferring the possession to the pledge creditor. In Serbian law, the two most common forms of non-possessory pledge are: mortgage on immovable property and registered pledge on movable assets and rights. The Mortgage Act prohibits certain restrictions on the pledge debtor, and the Act on Pledge on Movable Assets and Rights provides for possible restrictions on the debtor’s authorities through contractual clauses. The purpose of these restrictions is to additionally secure the legal position of the pledge creditor, without imposing an excessive burden on the pledge debtor. However, legal practice has shown that some of these restrictions are unnecessary, or that they impose an excessive burden on the pledge debtor from the moment of creating a pledge right to the moment of exercising that right (if it ensues). In this paper, the author addresses a number of related issues: which of these clauses are justified or unjustified, which of them unnecessarily weaken the position of the pledge debtor, whether they unnecessarily and disproportionately limit the pledge creditor, whether they are harmful for the credit system, etc.